Sleep facilitates consolidation of positive emotional memory in healthy older adults. Issue 3 (16th March 2019) - Gui, Wen-jun; Wang, Peng-yun; Lei, Xu; Lin, Tian; Horta, Marilyn; Liu, Xiao-yi; Yu, Jing
ABSTRACT: Evidence has demonstrated that sleep-related memory consolidation declines in ageing. However, little is known about age-related changes to sleep-related emotional memory consolidation, especially when considering the positivity effect observed in older adults. In the present study, we sought to explore whether there is a positive emotional bias in sleep-related memory consolidation among healthy older adults. Young and older adults were randomly assigned either into a sleep or wake condition. All participants encoded positive, negative, and neutral stimuli and underwent recognition tests immediately ( test 1 ), after a 12-hour sleep/wake interval ( test 2 ), and 3 days after test 2 ( test 3 ). Results showed that age-related differences of sleep beneficial effect were modulated by emotion valence. In particular, sleep selectively enhanced positive memory in older adults, while in young adults sleep beneficial effect was manifested in neutral memory. Moreover, the sleep beneficial effect can be maintained at least 3 days in both young and older adults. These findings suggest that older adults had preserved but positive bias of sleep-related memory consolidation, which could be one of the underlying mechanisms for their generally better emotional well-being in daily life. These findings highlight the dynamic interplay among sleep and emotional memory in older adults.